Field testing of a prototype mechanical dry toilet flush - Hennigs, Jan; Ravndal, Kristin T.; Blose, Thubelihle; Toolaram, Anju; Sindall, Rebecca C.; Barrington, Dani J.; Collins, Matt; Engineer, Bhavin; Kolios, Athanasios J.; McAdam, Ewan; Parker, Alison; Williams, Leon; et al. (Elsevier, 2019)
A prototype of a non-fluid based mechanical toilet flush was tested in a semi-public, institutional setting and in selected peri-urban households in eThekwini municipality, Republic of South Africa. The mechanism's functionality and users' perception of the flush were assessed. User perception varied depending on background: Users accustomed to porcelain water flush toilets were open to, yet reserved about the idea of using a waterless flush in their homes. Those who commonly use Urine Diversion Dehydration Toilets were far more receptive. The user-centred field trials were complemented by a controlled laboratory experiment, using synthetic urine, -faeces, and -menstrual blood, to systematically assess the efficiency of three swipe materials to clean the rotating bowl of the flush. A silicone rubber with oil-bleed-effect was found to be the best performing material for the swipe. Lubrication of the bowl prior to use further reduced fouling. A mechanical waterless flush that does not require consumables, like plastic wrappers, is a novelty and could – implemented in existing dry toilet systems – improve acceptance and thus the success of waterless sanitation.
Keywords: WASH; Reinvent the toilet challenge; Iterative design; User testing; Science-design Interface